Rape Culture and Religious Studies: Critical and Pedagogical Engagements - Graybill, Rhiannon; Minister, Meredith; Lawrence, Beatrice (Lexington Books, 2019)
Rape Culture and Religious Studies: Critical and Pedagogical Engagements stages a critical engagement between religious texts and the problem of sexual violence. Rape and other forms of sexual violence are widespread on college and university campuses; they also occur in sacred texts and religious traditions. The volume addresses these difficult intersections as they play out in texts, traditions, and university contexts. The volumegathers contributions from religious studies scholars to engage these questions from a variety of institutional contexts and to offer a constructive assessment of religious texts and traditions.